Osteogenesis Imperfecta: Bridging Genetic Insights with Clinical Signs– A Rare Case Report - Hancoro, Udi Herunefi; Zaidan, Marsa; Yanwar, Hikam; Timotius, Alson Bryant (eJournal Kedokteran Indonesia, 2025)
Osteogenesis Imperfecta (OI) is a rare genetic disorder affecting collagen production, leading to bone fragility and fractures. This case report aims to highlight the challenges and advancements in managing this condition. This report presents a rare case of a 13-year-old boy with OI, who experienced multiple fractures from minimal trauma, leading to mobility challenges. The patient first presented to Dr. Moewardi General Hospital, Surakarta, in June 2021, seeking evaluation for multiple bone fractures and mobility issues. Despite the absence of typical blue sclerae, the patient exhibited other OI symptoms such as dental growth disorders and a history of nine bone surgeries. Physical examination revealed bowing of the right lower limb and abnormal gait, while radiological findings confirmed bone deformities and fractures. OI results from mutations in the COL1A1 and COL1A2 genes, which are crucial for type I collagen synthesis. These genetic mutations lead to reduced bone density and increased fracture susceptibility. While clinical presentations vary, this patient did not exhibit blue sclerae or hearing loss. Diagnosis involves clinical and radiographic assessments, with bisphosphonates used for managing symptoms. OI remains a rare genetic disorder due to infrequent mutations in collagen-related genes. While bisphosphonates provide symptomatic relief, they do not cure the disease, highlighting the need for further research into treatments targeting the genetic etiology of OI.